STUDY ON URBAN ELDER MOBILE PHONE USERS IN CHINA: IN THE PERSPECTIVE OF AGING ISSUE - Law, Kian Aun (International Journal of Psychosocial Rehabilitation, 2020)
This thesis is from a total innovative perspective. In the existing literature research, the main research objective mostly focuses on the young generations while the elderly, as the main focus on the research of affecting factors of mobile phone usage, the function and application of design strategy for the elderly lacks the attention to their behaviors of mobile phone. In the early 21st century, China officially entered the aging society. Under the vast circumstance of a worsen aging society in China the proportion of the elderly will maintain a stable rising tendency therefore the elderly, as a consuming objective, is becoming to play an important role. According to the social trend of population aging and the expansion of the elderly population, some scholars began to focus on the economic consumption market of the elderly as a "gold mine to be mined", study the consumption behavior of the elderly, and put forward targeted marketing strategies to provide reference for enterprises to make marketing decisions. In the recent years, specific marketing research related to the elderly mainly focused on the fields of tourism, pension consumption, healthy products, however, information consumption still lagged behind others mentioned above. This paper starts with usage behaviors and preference of mobile phone of the elderly, researches on the big data, reflects the conducts of the elderly who use media, then analyses consumption features and preferences, and proposes strategy on database market. It will help to lay out future marketing strategy, to fill market demands more effectively, to improve the operator’s efficiency and economic benefits, which is of dramatic significance. In addition to this, it could inspire development and innovative design of APP, phone package and give references for related government, enterprises and research institutions.